The CAMH Neuroinformatics Platform: A Hospital-Focused Brain-CODE Implementation - Rotenberg, David J.; Chang, Qing; Potapova, Natalia; Wang, Andy; Hon, Marcia; Sanches, Marcos; Bogetic, Nikola; Frias, Nathan; Liu, Tommy; Behan, Brendan; El-Badrawi, Rachad; Strother, Stephen C.; et al. (Frontiers in Neuroinformatics, 2018)
Investigations of mental illness have been enriched by the advent and maturation of neuroimaging technologies and the rapid pace and increased affordability of molecular sequencing techniques, however, the increased volume, variety and velocity of research data, presents a considerable technical and analytic challenge to curate, federate and interpret. Aggregation of high-dimensional datasets across brain disorders can increase sample sizes and may help identify underlying causes of brain dysfunction, however, additional barriers exist for effective data harmonization and integration for their combined use in research. To help realize the potential of multi-modal data integration for the study of mental illness, the Centre for Addiction and Mental Health (CAMH) constructed a centralized data capture, visualization and analytics environment—the CAMH Neuroinformatics Platform—based on the Ontario Brain Institute (OBI) Brain-CODE architecture, towards the curation of a standardized, consolidated psychiatric hospital-wide research dataset, directly coupled to high performance computing resources.